Internalizing Islamic Ecotheology: An Ethnography of Communication Using the SPEAKING Framework at Lake Sipin - Ardiyansyah; Muhammad Al Hafizh; Ineke Nurrohimah; Zharifah Rukhaputri (INJECT (Interdisciplinary Journal of Communication), 2026)
This study explores environmental communication patterns and the internalization of ecotheological values ​​by the community of the Sipin Lake Ecotourism Area in maintaining the ecosystem of Sipin Lake in Jambi City. Although visual promotions have successfully increased tourist interest, the lake faces ecological challenges such as household waste and invasive weeds. This study uses a communication ethnography method with Dell Hymes' SPEAKING framework to analyze conversational events and communicative actions within the community. Data were collected through participant observation and in-depth interviews with the lakeside community in Legok Village. The results show that the community effectively internalizes ecotheology by framing environmental issues within religious narratives, such as "Cleanliness is part of faith" and "Nature is a divine mandate." This internalization occurs through informal conversations in raft houses and religious gatherings. This study finds that this spirituality-based communication bridges the gap between the community's economic needs and environmental conservation. This study contributes to environmental communication theory by highlighting the importance of religious identity in mobilizing local ecological action.